The Board and the Body: Material Constraints and Style in Graphic Narrative. Issue 1 (20th February 2019) - Grant, Pat
This article traces the development of grief memoir told in the language of comics. The autobiographical comic called Toormina Video is an occasion to investigate the role of the moving body in the process of creating graphic narratives. Cartooning can be seen as a performative mode of handwriting in which material rules and practical decisions constrain the drawing body and have a significant influence on the poetic and literary outcomes. The article demonstrates how graphic style in the comic book is in part the result of an antagonism between the literary impulse and the material restraints that structure the author's workflow. The comic under discussion is available to read online. Are we able to include a link to the work to enrich the experience? Toormina Video –http://www.patgrantart.com/toominavideo/toorminavideo.html . Blue –http://www.boltonblue.com/ .